Elevated temperature adhesion testing of spray‐applied fire‐resistive materials. (20th March 2015) - White, Christopher C.; Tan, Kar Tean; Hunston, Donald L.; Byrd, Eric W.
Summary: Effective fire protection of steel can be fully realized when spray‐applied fire resistive materials (SFRMs) are bonded sufficiently to structural steel during the event of a fire. The adhesion mechanisms and characterization at elevated temperatures, however, have remained elusive, owing to a shortage of quantitative experimental measurements of adhesion between SFRMs and structural steel. In complement with recent efforts aiming to measure the adhesion at ambient temperature, this contribution reports an experimental method based on a fracture mechanics approach to quantify temperature dependent adhesion behaviors of SFRMs adhered to steel substrates. Using this test method, it is shown that a sharp loss in adhesion occurs at temperatures well below 200 °C, and a less severe rate at higher temperatures. Thermogravimetric analysis and quasi‐state uniaxial compression tests reveal that SFRMs undergo pronounced losses in mass and modulus upon elevated temperature exposures, respectively. Additionally, the dependence of the bulk properties on temperature correlates strongly with that of fracture energy. A mechanism based on mechanical softening and dehydration of SFRMs is proposed to explain the thermally induced adhesion loss. Furthermore, a comparison with the ASTM E736 was made by invoking a fracture mechanics theory. Calculation of bond strengths reveals temperature dependence analogous to the fracture energy data. Also, the residual bond strengths above 150 °C fall below the threshold value (i.e., ≥ 7.2 kPa or 150 lb/ft 2 ) described in the ASTM E736. Importantly, the SFRMs are found to retain appreciable bond strengths greater than their own body masses, permitting them to remain intact in the event of a fire, in the absence of external perturbations. Published 2015. This article is a U.S. Government work and is in the public domain in the USA.